Statistical design and evaluation of a propranolol HCl gastric floating tablet - Meka Venkata Srikanth; Nali Sreenivasa Rao; Songa Ambedkar Sunil; Battu Janaki Ram; Venkata Ramana Murthy Kolapalli (Elsevier, 2012)
The purpose of this research was to apply statistical design for the preparation of a gastric floating tablet (GFT) of propranolol HCl and to investigate the effect of formulation variables on drug release and the buoyancy properties of the delivery system. The contents of polyethylene oxide (PEO) WSR coagulant and sodium bicarbonate were used as independent variables in central composite design of the best formulation. Main effects and interaction terms of the formulation variables were evaluated quantitatively using a mathematical model approach showing that both independent variables have significant effects on floating lag time, % drug release at 1 h (D1 h) and time required to release 90% of the drug (t90). The desired function was used to optimize the response variables, each with a different target, and the observed responses were in good agreement with the experimental values. FTIR and DSC studies of the statistically optimized formulation revealed there was no chemical interaction between drug and polymer. The statistically optimized formulation released drug according to first order kinetics with a non-Fickian diffusion mechanism. Evaluation of the optimized formulation in vivo in human volunteers showed that the GFT was buoyant in gastric fluid and that its gastric residence time was enhanced in the fed but not the fasted state.